Can we define migraine patients with blood high-sensitivity C-reactive protein and galectin-3 levels in the emergency department? - Gurger, Mehtap; Atescelik, Metin; Yilmaz, Mustafa; Yildiz, Mustafa; Kalayci, Hatice; Kobat, Mehmet Ali; Demir, Caner Fevzi (Termedia Publishing House Ltd, 2018)
Introduction: Migraine, the most widespread cause of headache in young adults, is a frequent reason for presentation to emergency departments. The aim of this study was to determine the diagnostic value of serum galectin-3 and high-sensitivity C-reactive protein (hsCRP) levels in migraine patients. Material and methods: Serum galectin-3 and hsCRP levels were measured using enzyme-linked immunosorbent assay in 70 migraine patients and 70 healthy control subjects. Results: The mean values of hsCRP and galectin-3 levels were significantly higher in the migraine group than those in the control group (1.67 +/- 0.49, 1.12 +/- 0.38 mg/l, p < 0.001; and 3.76 +/- 1.45, 2.05 +/- 0.29 ng/ml, p < 0.001, respectively). When the diagnostic values of the biomarkers were assessed in the migraine attack and control groups, the sensitivity and specificity of the test for hsCRP at the cut-off point of 1.32 mg/l were 70% and 73% (AUC = 0.805, 95% CI: 0.74-0.88, p < 0.001), and for galectin-3 at the cut-off point of 2.4 ng/ ml, 89% and 90% (AUC = 0.97, 95% CI: 0.95-0.99, p < 0.001), respectively. Conclusions: This study showed the presence of a relation between high serum levels of hsCRP and galectin-3 in migraine patients. However, well-controlled, carefully executed longitudinal studies are required to confirm these findings.
Keywords: galectin-3; high-sensitivity C-reactive protein; migraine